2018
DOI: 10.1021/acsami.8b15746
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Characterization of the Triphase Contact Line in a Brush-Coating Process: Toward the Enhanced Efficiency of Polymer Solar Cells

Abstract: Solution processes have been widely used for making polymer films in organic photoelectric devices but suffer from difficulties in controlling the film formation. Here, by in situ characterization triphase contact lines (TCLs) in a brush-coating process, we clarify how TCLs affect the quality of as-prepared films. By fine-tuning the dewetting of a binary polymer solution (P3HT:PCBM) via different directions, TCLs with different patterns lead to films with different morphologies. High-quality nanothin films wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
(42 reference statements)
2
26
0
Order By: Relevance
“…By linear fitting, curves of V drop vs. t gave different slopes (Figure 4 i), suggesting the solvent evaporation speed of | K QD |=1.759 > | K ZnO |=0.929 > | K TFB |=0.649 > | K PEDOT:PSS |=0.287. For the solution with a high evaporation speed, the writing speed should be appropriately increased to match the movable TCL [16] . Based on the evaporation speed, v QD > v ZnO > v TFB > v PEDOT:PSS was deduced, essentially in accordance with experimental results.…”
Section: Figuresupporting
confidence: 69%
See 2 more Smart Citations
“…By linear fitting, curves of V drop vs. t gave different slopes (Figure 4 i), suggesting the solvent evaporation speed of | K QD |=1.759 > | K ZnO |=0.929 > | K TFB |=0.649 > | K PEDOT:PSS |=0.287. For the solution with a high evaporation speed, the writing speed should be appropriately increased to match the movable TCL [16] . Based on the evaporation speed, v QD > v ZnO > v TFB > v PEDOT:PSS was deduced, essentially in accordance with experimental results.…”
Section: Figuresupporting
confidence: 69%
“…With enlarging N fiber from 3 (Figure S2) to 25 (Figure 4 e), the uniform velocity distribution in the liquid film remain unchanged, suggesting non‐deteriorated uniformity as the film area increases. On the other hand, the writing speed affects the length of the transition area, as well as the duration time for self‐assemble [16] . The uniform boundary can be obtained under a suitable speed (Figure 4 f), as has been validated by the weak reflux and the uniform velocity distribution when setting the length ( L ) of the liquid film as 200 μm (Figure 4 g).…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, the writing speed affects the length of the transition area, as well as the duration time for self-assemble. [16] The uniform boundary can be obtained under a suitable speed (Figure 4 f), as has been validated by the weak reflux and the uniform velocity distribution when setting the length (L) of the liquid film as 200 mm (Figure 4 g). If L is too long (namely, the speed is too fast), mountain-like deposits form at the boundary (Figure 4 f), agreeing well with the strong reflux and the nonuniform fluidic velocity when setting L as 1000 mm (Figure 4 h).…”
Section: Angewandte Chemiementioning
confidence: 63%
“…25(p25) Kim et al 88 used a nylon brush to deposit the active layer (P3HT:PCBM) of an OPV and concluded that this is a simple, low-cost and promising technique for the production of large areas on a large scale. The brush coating was applied to the coating of the AgNWs anode in the studies, 54,122 CNT in the studies, 58 of the PEDOT:PSS hole transport layer in the study, 122 of the active layer P3HT:PCBM in the studies, 88,122,123 of the ZnO electron transport layer. 122…”
Section: Brush Coatingmentioning
confidence: 99%